2006
DOI: 10.1200/jco.2006.24.18_suppl.8634
|View full text |Cite
|
Sign up to set email alerts
|

Effect of wheat grass juice in supportive care of terminally ill cancer patients— A tertiary cancer centre experience from India

Abstract: 8634 Background: The solid content of juice made from wheat grass is 70% chlorophyll. Chlorophyll is often referred to as “The blood of plant life” and has almost the same chemical structure as haemoglobin. Chlorophyll cleanses the blood by improving the supply of oxygen to the circulatory system. Wheat grass is also a complete protein with about 30 enzymes, vitamins & minerals. Wheat grass juice has been proven over many years to benefit people in numerous ways, building the blood, restoring balance in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…(Walters, 1992). Increase in vitamins, ferulic acid and vanillic acid content with increase in germination period results in increase in antioxidant potential (Dey et al, 2006). Wheatgrass acts as a de-toxificant, stimulates metabolism and reduces acidity of the blood.…”
Section: Introductionmentioning
confidence: 99%
“…(Walters, 1992). Increase in vitamins, ferulic acid and vanillic acid content with increase in germination period results in increase in antioxidant potential (Dey et al, 2006). Wheatgrass acts as a de-toxificant, stimulates metabolism and reduces acidity of the blood.…”
Section: Introductionmentioning
confidence: 99%
“…Its role in cancer is well-documented [20]. Wheat grass juice is suggested to be an effective alternative to blood transfusion and in terminally ill cancer patients, it should be encouraged [21]. It prevents deterioration of hematological parameters (Hemoglobin and platelet count) produced by anticancer therapy and decreases the number of blood transfusions requirements in cancer patients [22].…”
Section: Discussionmentioning
confidence: 99%
“…34 In another study, Dey et al found that wheat grass juice helped to improve the health status and lifespan in terminally ill cancer patients. 35 The extract of wheat grass when applied to known chemical mutagens, decreased their cancer causing ability by up to 99% [36][37] which suggests that wheat grass may have cancer preventing property. These studies were primarily in vitro and its extrapolation into in vivo situations are needed to make more conclusive statements.…”
Section: Evaluation Of Hypothesismentioning
confidence: 99%